Research on kinematics and attitude control model of a surgical interventional catheter. (12th September 2019) - Xu, Zhenyu
To solve the problems of poor versatility and inactivity of the traditional interventional catheters, a forward kinematic model of multi-segment catheters in series is established by using D-H parameter method, which is based on the geometrical structure of the designed catheters. In order to ensure the decoupling control of the driver's length, we look into the relationship between the driver's length and the posture of the catheter unit. The control model of the catheter's posture is further presented, in which the characteristics of driver is equivalent to the arc shape. Finally, the fuzzy Proportional-Integral-Differential Control (PID) control is designed to control the catheter unit which greatly improves the precision of the control model. The results show that the relationship between the predicted driver length and the catheter attitude angle is basically consistent with the experimental results, which verifies the effectiveness of the variable universe fuzzy PID control.